2007 IEEE/WIC/ACM International Conferences on Web Intelligence and Intelligent Agent Technology - Workshops 2007
DOI: 10.1109/wiiatw.2007.4427596
|View full text |Cite
|
Sign up to set email alerts
|

Learn to Detect Phishing Scams Using Learning and Ensemble ?Methods

Abstract: Phishing attack is a kind of identity theft which tries to steal confidential data like on -line bank account information . In a phishing attack scenario, attacker deceives users by a fake email which is called scam. In this paper we employ three different learning methods to detect phishing scams. Then, we use ensemble methods on their results to improve our scam detection mechanism. Experimental results show that the proposed method can detect 94.4% of scam emails correctly, while only 0.08% of legitimate em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…This technique achieved a recall level of 100% and a precision that was slightly higher than that of C5.0 (although not significantly so). Saberi et al [18] used a classifier ensemble to detect phishing scams. The ensemble employs a simple consensus technique in order to combine the results of the K-NN, poisson probability distributions and naïve bayes algorithms in order to boost performance of the system.…”
Section: Related Workmentioning
confidence: 99%
“…This technique achieved a recall level of 100% and a precision that was slightly higher than that of C5.0 (although not significantly so). Saberi et al [18] used a classifier ensemble to detect phishing scams. The ensemble employs a simple consensus technique in order to combine the results of the K-NN, poisson probability distributions and naïve bayes algorithms in order to boost performance of the system.…”
Section: Related Workmentioning
confidence: 99%
“…Another widely deployed technique used multi classifier related with machine learning for phishing email detection is (Saberi et al, 2007), the proposed method accuracy detected 94.4% of phishing emails. An another approach depend on three tier classification to detect phishing emails is (Islam et al, 2009), if the first two classifier can't classify well the final tier will have the final decision , the average accuracy of this approach reach up to 97%.…”
Section: Methodsmentioning
confidence: 99%
“…There are other defensive mechanisms, such as preventing a phishing attack from reaching its intended recipient [13], [14]. However, it has been shown that there is a need to better protect victims from phishing attacks, as blacklists are not working [15].…”
Section: B Motivationmentioning
confidence: 99%